Promoting early presentation of breast cancer: a preliminary evaluation of a written intervention. (March 2014) - Forster, Alice S; Forbes, Lindsay JL; Abraham, Charles; Warburton, Fiona G; Douglas, Elaine; Ramirez, Amanda-Jane
Objectives: Older women are more likely to delay presentation with breast cancer, which contributes to poorer survival. We evaluated a written intervention that was designed to provide women with the knowledge, motivation, confidence and skills to present promptly with breast cancer symptoms. Methods: We assessed acceptability and understanding of the intervention by interviewing 43 women. We used their responses to refine the intervention. We tested the effect of the intervention on breast cancer awareness, confidence and intentions to check breasts and perceived barriers to help-seeking using a self-report questionnaire administered to 61 women prior to and one month after receiving the intervention. Quantitative data were analysed using the McNemar test. Results: Women were not made anxious by the intervention and understood its messages. At one month, a greater proportion of women knew that breast cancer risk increases with age, identified ≥5 non-lump symptoms and reported breast checking at least monthly in comparison to before the intervention was implemented. Discussion: The intervention does not induce anxiety, is understandable, and appears to increase breast cancer awareness. The results provide justification for a more rigorous trial to test efficacy.